ЗАРУБІЖНИЙ ДОСВІД ДИФЕРЕНЦІАЦІЇ КРИМІНАЛЬНОЇ ВІДПОВІДАЛЬНОСТІ ЗА СТВОРЕННЯ ЗЛОЧИННИХ ОБ’ЄДНАНЬ ТА УЧАСТЬ В НИХ - Вознюк, Андрій Андрійович (SUPREMANCE OF LAW, 2017)
The article deals with the comparative and legal study of the features of the differentiation of criminal responsibility for the creation of criminal association and participation in them in the criminal legislation of foreign countries. It is spoken in detail about the existing models of such distribution of criminal responsibility in the world are revealed. The article gives a detailed analysis of their classification. Much attention is given to some advantages and disadvantages of different approaches to the differentiation of criminal responsibility are described. Some advantages and disadvantages of different approaches to the differentiation of criminal responsibility are described in the article.
Keywords: differentiation of criminal responsibility; aggravating circumstances of a crime and especially aggravating circumstances of a crime; criminal association; organized group; criminal organization; gang; terrorist associations; illegal paramilitary or armed formation; complicity in a crime